WEAR PERFORMANCE OF ALUMINA-ZIRCONIA, ALUMINA-ZIRCONIA-CHROMIA AND ALUMINA-ZIRCONIA-MAGNESIA IN MACHINING AISI 1045 STEEL - Azhar, Anis Afuza; Abu Bakar, Mohd Hadzley; Haji Azlan, Umar Al-Amani; TAMIN, NORFAUZI; Mohd Rashid, Mohd Fairuz; Herawan, Safarudin Gazali (Malaysian Tribology Society (Mytribos), 2022)
Cutting tools is very important in determining productivity in machining operation. Small changes in formulation of cutting tools could promotes different performance in tool life and wear mechanism. This study compares wear performance of Alumina-Zirconia (80-20 wt%), Alumina-Zirconia-Chromia (80-20-0.6 wt%) and Alumina-Zirconia-Magnesia (80-20-0.2 wt%) cutting tools. The cutting tools were fabricated with powder metallurgy process and machining trials were performed with AISI 1045 at 250 m/min cutting speed, 0.125 mm/rev feed rate ad 0.5 mm depth of cut. The results reveal that Alumina-Zirconia-Magnesia cutting tools can last up to 298 s, which is 42% longer than AluminaZirconia-Chromia and 413% longer than AluminaZirconia. Both Alumina-Zirconia-Chromia and AluminaZirconia-Magnesia cutting tools exhibited nearly identical wear mechanisms, with uniform flank wear at the tool edge linked with lower friction and temperature when engaged with workpiece material. For Alumina-Zirconia cutting tool, wear mechanism dominated by severe chipping and fracture.